PENGARUH PSIKOEDUKASI MENOPAUSE DAN RELAKSASI UNTUK MENURUNKAN KECEMASAN WANITA PRE MENOPAUSE - Sriwaty, Ida; Nuryoto, Sartini (Universitas Ahmad Dahlan, 2015)
AbstractObjective of this research is to see whether psychoeducation and relaxation can reduce anxiety in pre-menopausal women. Subjects of the research are women live in villages in Yogyakarta, they experience pre-menopausal symptoms such as irregular menstrual cycles in the 6 months or at the last-1 year and experience hot flashes, sweating at night and sleep disorders. subjects were divided into two groups: an experimental group which consisted of 6 subjects and the control group consisted of 5 subjects. Data collection tool used in this research is the anxiety scale TMAS (Taylor manifest anxiety scale). Data wereanalyzed using non-parametric test with Mann Whitney and Wilcoxon test. It showed that the experimental group obtained significant results with values p = 0.027 (p <0.05) and the Z value is -2.207 while the control group showed no significant results with p = 0.102 (p> 0.05) and the Z value is -1.633. The Mann Whitney test showed significant values 0.021 and Z value is -2.303. In conclusion the provision of psychoeducation and relaxation menopause can reduce anxiety in pre-menopausal women.Keywords: anxiety, psychoeducation, relaxation, premenopausal